Integrasi Fiskal Digital Daerah: Strategi Meningkatkan PAD dan Akuntabilitas Keuangan Publik - Sulistyowati, Ani (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2025)
As of May 2025, Ministry of Home Affairs data indicates that more than 29 local governments have yet to fully operationalize the revenue module within the National Integrated Local Government Information System (SIPD RI). Furthermore, 74% of regions continue to utilize multiple fragmented financial information systems, despite the mandatory adoption of SIPD RI mandated since early 2024. This high dependency on central government transfer funds not only reflects a lack of local fiscal potential exploration but also points to structural issues in regional revenue governance (Bappenas, 2023). An analysis of Local Own-Source Revenue (PAD) trends from 2021–2025 shows stagnant contributions in many regions, with averages remaining below 20% of the total Regional Budget (APBD). While the Ministry of Home Affairs’ SIPD Grand Design for 2022–2025 targets full integration between revenue, expenditure, and accounting modules, technical and regulatory hurdles at the local level persist. Despite the existence of Ministry of Home Affairs Regulations (Permendagri) No. 70 of 2019 and No. 77 of 2020 as foundations for digital financial management, the lack of technical regulations governing a national digital fiscal system architecture has resulted in fragmented, siloed local applications. This creates risks of data redundancy, inefficient recording processes, and weak oversight of PAD achievements.